Pesantren-Based Leadership Management in Strengthening Organizational Culture at Madrasah Ibtidaiyah - Nur Qomariah (Program Studi Doktor Manajemen Pendidikan Islam, Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study examines how leadership management in a pesantren-based madrasah strengthens organizational culture through the integration of managerial functions and pesantren values. A qualitative case study was conducted at MI Walisongo Gempol, Pasuruan, involving one principal, two teachers, and one education staff member selected purposively. Data were collected through participatory observation, semi-structured in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing and verification. The findings reveal four interconnected patterns. First, shura is operationalized through participatory planning and collective decision-making, strengthening shared commitment and organizational ownership. Second, amanah provides an ethical foundation for task distribution, delegation, responsibility, and accountability. Third, tarbiyah shapes supervision as a developmental process that combines professional guidance, reflection, and continuous improvement. Fourth, uswah hasanah functions as a mechanism for internalizing discipline, integrity, religiosity, responsibility, and organizational commitment through exemplary leadership. Based on these findings, the study formulates the Pesantren-Based Leadership Management for Organizational Culture (PBLM-OC) framework, which explains the processual relationship among pesantren values, management functions, leadership practices, and organizational culture. The study contributes to Islamic educational management by positioning pesantren values as operational principles within leadership management rather than merely normative institutional attributes.